2013
DOI: 10.1186/1479-5876-11-158
|View full text |Cite
|
Sign up to set email alerts
|

A multi-site feasibility study for personalized medicine in canines with Osteosarcoma

Abstract: BackgroundA successful therapeutic strategy, specifically tailored to the molecular constitution of an individual and their disease, is an ambitious objective of modern medicine. In this report, we highlight a feasibility study in canine osteosarcoma focused on refining the infrastructure and processes required for prospective clinical trials using a series of gene expression-based Personalized Medicine (PMed) algorithms to predict suitable therapies within 5 days of sample receipt.MethodsTumor tissue samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 47 publications
(61 reference statements)
0
13
0
Order By: Relevance
“…The first PMed system (used for the Study 1 drug predictions) was developed internally at VARI and include a list of 188 compounds both developmental and FDA approved. The later PMed system (Intervention Insights—used in Study 2), is a system that evolved from the original software to be used for human patients and therefore included only 183 FDA approved drugs along with the addition of the Biomarker Rules . The five methods utilized in this report include expression based methods, drug target expression (raw score) and drug sensitive/resistant biomarker rules .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The first PMed system (used for the Study 1 drug predictions) was developed internally at VARI and include a list of 188 compounds both developmental and FDA approved. The later PMed system (Intervention Insights—used in Study 2), is a system that evolved from the original software to be used for human patients and therefore included only 183 FDA approved drugs along with the addition of the Biomarker Rules . The five methods utilized in this report include expression based methods, drug target expression (raw score) and drug sensitive/resistant biomarker rules .…”
Section: Methodsmentioning
confidence: 99%
“…The methods for predicting suitable therapies based on the RNA analyte have been described in detail previously and are currently being used in both human (FDA approved) and canine clinical trials. As a brief overview, the PMed system utilized in this study is a conglomeration of five predictive methodologies which predict suitable drugs based on the RNA expression data, subsequently ranking these based on the strength of prediction (target expression) combined with the number of targets and number of methods that predict a given drug.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, different responses can be considered to be differentially affect the phenotype of these cells. Therefore, the tumors gene expression analysis could elucidate new therapeutic targets leading to personalized treatments, as presented by the study of Monks et al [16] which showed that it is possible to provide a report to the veterinarian from a single biopsy from amputation of the affected limb within 5 days. In relation to the study by O'Donoghue et al [6], we explored differences in gene expression between primary tumors of OSA of dogs with disease-free interval (DFI) less than 100 days and greater than 300 days after chemotherapy.…”
Section: Molecular Biology and The Search Of Biomarkers Of The Tumoramentioning
confidence: 99%
“…Ultimately, gene expression patterns from individual tumours may direct personal patient treatment plans, using therapy targeted to specific pathways of gene expression (Chantrill et al, 2015). The feasibility of prospective molecular profiling of canine cancers for personalised medicine (PMed) has already been investigated successfully, making it a practical option for clinical use (Monks et al, 2013;Paoloni et al, 2014). In the shorter term, genomic profiling can usefully identify a few key genes for which IHC or RT-PCR assays can be developed for clinical diagnostic use.…”
Section: Introductionmentioning
confidence: 99%